2019
DOI: 10.1002/ca.23526
|View full text |Cite
|
Sign up to set email alerts
|

Localized Rotator Cuff Tendon Degeneration for Cadaveric Shoulders with and Without Tears Isolated to the Supraspinatus Tendon

Abstract: Localized differences in tissue degeneration throughout intact and torn rotator cuff tendons have not been well quantified. The objective of this study was to investigate histological differences in localized degeneration in tendons with and without rotator cuff tears isolated to the supraspinatus tendon. Four intact shoulders and four shoulders with rotator cuff tears isolated to the supraspinatus tendon were dissected down to the infraspinatus and supraspinatus tendons. Biopsies were taken throughout the ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…With respect to the latter, the morphological appearance of regions 3 and 4 in Figure 3 and regions B and C in Figure 4 - 15 is in line with descriptions of the morphological appearance of degenerative supraspinatus tendon tissue at various degrees in the literature[ 49 - 51 ]. Additionally, to our knowledge, spots within tendons with morphological appearance and immunohistochemical characterization as the one observed in the second part of the biopsy (Panels D in Figure 4 - 15 ) have not previously been described in the scientific literature.…”
Section: Discussionsupporting
confidence: 85%
“…With respect to the latter, the morphological appearance of regions 3 and 4 in Figure 3 and regions B and C in Figure 4 - 15 is in line with descriptions of the morphological appearance of degenerative supraspinatus tendon tissue at various degrees in the literature[ 49 - 51 ]. Additionally, to our knowledge, spots within tendons with morphological appearance and immunohistochemical characterization as the one observed in the second part of the biopsy (Panels D in Figure 4 - 15 ) have not previously been described in the scientific literature.…”
Section: Discussionsupporting
confidence: 85%
“…With respect to the latter, the morphological appearance of regions 3 and 4 in Figure 3 and regions B and C in Figures 4-15 is in line with descriptions of the morphological appearance of degenerative supraspinatus tendon tissue at various degrees in the literature [49][50][51] . Additionally, to our knowledge, spots within tendons with morphological appearance and immunohistochemical characterization as the one observed in the second part of the biopsy (Panels D in Figures 4-15) have not previously been described in the scientific literature.…”
Section: Discussionsupporting
confidence: 85%
“…In the cadaveric study by Ferrer et al, 6 similar amounts of tendon degeneration parameters (cellularity, fiber organization, and nuclei shape) were observed for intact and torn supraspinatus tendons, indicating that tendon degeneration likely occurs before the RC tear. Another cadaveric study showed similar results.…”
Section: Discussionmentioning
confidence: 72%
“…However, a previous cadaveric study demonstrated that no significant differences were observed in degeneration, fiber organization, nuclei shape, and cellularity by location (insertion, midsubstance, myotendinous junction, and the medial, anterior, and posterior edges of the tear). 6 Fourth, the evaluation of clinical findings in this study was based on the UCLA score, which was originally designed to evaluate shoulder arthroplasty, although there are reports of its use for RC surgery. 1,27 Fifth, the postoperative follow-up period was relatively short for the analysis of clinical outcomes after surgery.…”
Section: Discussionmentioning
confidence: 99%